Effect of varying accelerometry criteria on physical activity: The look ahead study1. (16th March 2013) - Miller, Gary D.; Jakicic, John M.; Rejeski, W. Jack; Whit‐Glover, Melicia C.; Lang, Wei; Walkup, Michael P.; Hodges, Mimi L.
Abstract: The importance of physical activity in weight management is widely documented. Although accelerometers offer an objective measure of activity that provide a valuable tool for intervention research, considerations for processing these data need further development. Objective: This study tests the effects of using different criteria for accelerometry data reduction. Design and Methods: Data were obtained from 2, 240 overweight and obese individuals with type 2 diabetes mellitus (T2DM) from the Look AHEAD study, with 2, 177 baseline accelerometer files used for analysis. Number, duration, and intensity of moderate (≥3 metabolic equivalents (METS)) and vigorous (≥6 METS) activity bouts were compared using various data reduction criteria. Daily wear time was identified as 1, 440 min/day minus non‐wear time. Comparisons of physical activity patterns for non‐wear time (using either 20, 30, or 60 min of continuous zeros), minimal daily wear time (8, 10, and 12 h), number of days with available data (4, 5, and 6 days), weekdays vs. weekends, and 1‐ or 2‐min time interruptions in an activity bout were performed. Results: In this mostly obese population with T2DM (BMI = 36.4 kg/m 2 ; mean age = 59.0 years), there were minimal differences in physical activity patterns using the different methods of data reduction. Altering criteria led to differences in the number of available data (sample size) meeting specific criteria. Conclusions: Although our results are likely directly applicable only to obese individuals with T2DM, an understudied population with regards to physical activity, the systematic analysis for data reduction employed can be more generalizable and provide guidance in this area in the absence of standard procedures.